Assessment of Soil Erosion Impacts at the Panchhari Sub-district of Chittagong Hill Tracts in Bangladesh Using Remote Sensing and GIS Techniques Based on RUSLE Model - Rathindra Nath Biswas; M. Nazrul Islam; Samia Islam (International Journal of Climate Conditions, 2024)
Soil erosion has been identified as a significant issue around the world. It is often exacerbated due to land deterioration, conversion of agricultural land, and other anthropogenic activities. It negatively impacts soil productivity, water quality deterioration, river and reservoir bed sedimentation, nutrient loss, and sustainability of natural resources. Understanding the controlling factors of soil erosion can help us to identify erosion-prone areas and improve land use management. The novelty of the present research is to explore spatial patterns of soil loss through sophisticated GIS and RS technology for sustainable management of the forest landscape of Bangladesh. To approximate of the mean annual soil loss at the Panchhari Upazila under Chittagong Hill Tract (CHTs), present study applied RUSLE approaches by using remotely sensed data, climate variable and lithology information. The climate of the Chittagong Hill Tracts, particularly in Panchari Upazila, was influenced by a tropical monsoon climate with abundant rainfall. The RUSLE model's findings show that the yearly average soil loss in the studied region fluctuated from 0 to 108517 t ha-1 y-1. The probability map of soil erosion shows that roughly 0.71%, 4.02%, 61.26%, and 34.01% of the region fall into the low, moderate, and high erosion categories, respectively. The goal of the study is to fulfill the personnel duties of many different sectors, including those of environmental managers, agriculturalists, water resource managers, ecologists, geologists, geomorphologists, and socio-hydrologists for the implementation of development initiatives and implementation of sustainable development management strategies for the forest landscape. Geomorphometric analysis and a computation of the region's sediment production will be part of further research for ecological development and long-term watershed management.
Keywords: Bangladesh; Forest Landscape; RUSLE Model; geographic information system (GIS); remote sensing; soil erosion